2022
DOI: 10.1109/access.2022.3199409
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of a Unique Cell Selection Phenomenon in Public Unlicensed Cellular Networks Through Machine Learning

Abstract: Cellular operators deploy 4G License Assisted Access (LAA) and 5G NR-U base stations in the unlicensed spectrum, to enhance the overall network capacity. This work highlights a unique Physical Cell Id (PCI) related phenomenon observed in the public LAA operator deployments. Notably, the licensed and unlicensed carriers of a device may have the same PCI or different PCIs. The phenomenon is triggered by the combined effect of unlicensed deployment architectures and cell selection mechanisms. Consequently, the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Nevertheless, the study does not thoroughly explore the influence of coexistence on quality of service (QoS) metrics i.e., the impact of coexistence on parameters such as latency, packet loss, and other QoS factors that would enhance a comprehensive understanding of LTE-LAA coexistence with WiFi systems. The impact of a unique phenomenon related to Physical Cell Id (PCI) on integrated system including LTE, LAA, and Wi-Fi is demonstrated in [23] using machine learning algorithms. Although [23] contributes significantly to enhance LTE-LAA coexistence with WiFi systems, the study does not explicitly examine the impact of varying user densities on the observed PCI scenarios.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the study does not thoroughly explore the influence of coexistence on quality of service (QoS) metrics i.e., the impact of coexistence on parameters such as latency, packet loss, and other QoS factors that would enhance a comprehensive understanding of LTE-LAA coexistence with WiFi systems. The impact of a unique phenomenon related to Physical Cell Id (PCI) on integrated system including LTE, LAA, and Wi-Fi is demonstrated in [23] using machine learning algorithms. Although [23] contributes significantly to enhance LTE-LAA coexistence with WiFi systems, the study does not explicitly examine the impact of varying user densities on the observed PCI scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…The impact of a unique phenomenon related to Physical Cell Id (PCI) on integrated system including LTE, LAA, and Wi-Fi is demonstrated in [23] using machine learning algorithms. Although [23] contributes significantly to enhance LTE-LAA coexistence with WiFi systems, the study does not explicitly examine the impact of varying user densities on the observed PCI scenarios. Particularly in scenarios marked by high traffic density, fluctuations in the dynamics of coexistence and PCI-related effects may vary, which may potentially affect the robustness of identified solutions.…”
Section: Related Workmentioning
confidence: 99%
“…ML algorithms derive insights from raw data gathered through measurements and are better suited for comparing cellular network scenarios and contexts [6]. For example, two cell selection scenarios were identified in current unlicensed networks, which was not evident from the measurement-based analysis [7]. Network performance optimization can also benefit from datadriven inputs.…”
Section: Introductionmentioning
confidence: 99%